ANALYSIS OF CAREER AND ALUMNI CENTER WEBSITE USING DELONE AND MCLEAN MODELS BASED ON ALUMNI PERCEPTION OF DYNAMICS UNIVERSITY SURABAYA - Irfan listyo Pamungkas; sulis tiowati; Tony Soebijono (Jurnal Sistem Informasi Universitas Dinamika, 2020)
Surabaya dynamics university career and alumni service centers have a career and alumni service center website. The website is a digital information specifically for Surabaya dynamics university alumni with an online system released in 2008. The career center and alumni university Surabaya dynamics services website ranks 3,395 in Indonesia according to Alexa with the Uniform Resource Locator (URL) www.alexa.com. After the career center and alumni website has been implemented, there has never been an evaluation of the system quality, information quality and service quality of the career center and alumni website based on the end-user perception as feedback to the website manager.Based on the existing problems, by analyzing the success of the career service center website and alumni as an evaluation material and input or consideration material for the career service center and alumni of Surabaya dynamics university in knowing the quality of the system, the quality of information and the quality of service. This success analysis uses the information system success method of DeLone and McLean by analyzing the variables of System Quality, Information Quality, Service Quality, Usage, User Satisfaction, and Net Benefits from the career center and alumni service center website.The results of the study by distributing questionnaires to a sample of 137 alumni, showed that the System Quality variable had a positive and significant effect on User Satisfaction. Service Quality Variables have a positive and significant effect on Usage. The User Satisfaction variable has a positive and significant effect on Net Benefits. And the Service Quality variable has a significant influence on the Net Benefit variable through the mediation variable. So the Surabaya dynamics university career and alumni service center should further improve digital service information related to job vacancies, and the website service system of the career and alumni center of Surabaya Dinamika University.